2019
DOI: 10.3390/molecules24071429
|View full text |Cite
|
Sign up to set email alerts
|

Primary Step Towards In Situ Detection of Chemical Biomarkers in the UNIVERSE via Liquid-Based Analytical System: Development of an Automated Online Trapping/Liquid Chromatography System

Abstract: The search for biomarkers in our solar system is a fundamental challenge for the space research community. It encompasses major difficulties linked to their very low concentration levels, their ambiguous origins (biotic or abiotic), as well as their diversity and complexity. Even if, in 40 years’ time, great improvements in sample pre-treatment, chromatographic separation and mass spectrometry detection have been achieved, there is still a need for new in situ scientific instrumentation. This work presents an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…For example, benchtop LC-MS was used to detect amino acids, dipeptides, and sugars from a cometary ice analog (Eddhif et al, 2018). A similar study that also incorporated a trap-column prior to separation, also known as column-switching methodology, showed that amino acids, oligopeptides, and nucleobases could be separated and detected at approximately 1 μg/L (Ribette et al, 2019). Liu et al (2008) used ion-pair reversed-phase LC coupled with MS to detect underivatized amino acids with instrument LODs ranging from 3 μg/L to 800 μg/L.…”
Section: Astrobiology Applications and State-ofthe-artmentioning
confidence: 99%
“…For example, benchtop LC-MS was used to detect amino acids, dipeptides, and sugars from a cometary ice analog (Eddhif et al, 2018). A similar study that also incorporated a trap-column prior to separation, also known as column-switching methodology, showed that amino acids, oligopeptides, and nucleobases could be separated and detected at approximately 1 μg/L (Ribette et al, 2019). Liu et al (2008) used ion-pair reversed-phase LC coupled with MS to detect underivatized amino acids with instrument LODs ranging from 3 μg/L to 800 μg/L.…”
Section: Astrobiology Applications and State-ofthe-artmentioning
confidence: 99%
“…However, the environment believed to exist on Europa and Enceladus may also hinder the implementation of this approach because the H 2 O 2 could interfere with the breakdown of organic molecules during the pyrolysis step (Benner et al, 2000;Navarro-González et al, 2006). To address this limitation, a number of liquid-based analytical techniques have been proposed (Blanco et al, 2017;Ribette et al, 2019). Out of those, immunoassays, electrochemical sensors (Thomson et al, 2020), and microfluidic capillary electrophoresis technologies hold the most promise in terms of power requirement, weight, sensitivity, and ability to detect biomarkers in model systems (Derveni et al, 2012;Sims et al, 2012;Willis et al, 2012;Butterworth et al, 2015;Mathies et al, 2017Mathies et al, , 2019Moreno-Paz et al, 2018;García-Descalzo et al, 2019;Lezcano et al, 2019).…”
Section: Introductionmentioning
confidence: 99%